ANALISIS EKSPOR IMPOR KOMODITAS PERTANIAN MELALUI PLBN ARUK TAHUN 2023–2024 DALAM PERSPEKTIF EKONOMI ISLAM - Harly, Abtar; Hutagaluh, Oskar; Desi Yuniarti (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This study aims to analyze the development of agricultural commodity exports and imports through the Aruk State Border Post (PLBN Aruk) during 2023-2024 and to examine their implications from the perspective of Islamic economics. The research employs a descriptive and explanatory quantitative approach using a log-log linear regression model and SWOT analysis. The data utilized are secondary data obtained from the Foreign Trade Statistics of West Kalimantan Province published by Statistics Indonesia (BPS). The findings indicate that export volume declined by 29.27%, while export value decreased by 44.50%. The regression estimation shows an elasticity coefficient of 0.955 (p < 0.01), implying that a 1% increase in export volume leads to a 0.955% increase in export value. The export structure remains dominated by primary commodities, particularly fruits and fisheries products. From the perspective of Islamic economics, these findings highlight the importance of strengthening the real sector, enhancing value-added through the integration of halal supply chain systems, and promoting sharia-based financing to improve the welfare of border communities. This study contributes to the formulation of a border trade development model grounded in Islamic economic principles, emphasizing maslahah and sustainability.